Aplikasi Akad Tabarruâ Wadiâah dan Qard di Perbankan Syariah - Hayati, Ilda (AL-FALAH : Journal of Islamic Economics, 2016)
The economic transaction in Islam is not always to orientate on commercial, and profit-oriented activity. It is namely with tabbaruââall of agreement intentionally related to non-profit. The âaqd can be an activity of which gives or borrows something. In fact, especially in Islamic Bank, that âaqd is consistently maintained in the tabbaruâ principles. The existed-cost in conserving, is obviously as an avoindance-compentation. The paper will examine the wadiâah concept and qard in Islamic Bank. Keywords: Application, Tabbaruâ âAqd, Wadiah, Qard and Islamic Bank.